Suppression of Gingival NK Cells in Precancerous and Cancerous Stages of Pancreatic Cancer in KC and BLT-Humanized Mice - Kaur, Kawaljit; Chang, Hui-Hua; Cook, Jessica; Eibl, Guido; Jewett, Anahid (Frontiers in Immunology, 2017)
The aim of our studies is to determine the dynamics of NK cell modulation in gingivae in pre-cancerous and cancerous stages of pancreatic and oral cancers in P48+/Cre;LSL-KRASG12D (KC) mice carrying a pancreas-specific oncogenic Kras mutation and BLT-humanized mice. Wild type and KC mice fed with control diet (CD) or high fat calorie diet (HFCD), and the pancreatic and oral tumor-bearing humanized BLT (hu-BLT) mice were used to determine pre-cancerous and cancer induced changes in numbers and function of gingival NK cells. Increased numbers of PanIN lesions and the greatest score of inflammation in pancreas of KC mice fed with CD and HFCD co-related with significant decline in percentages of circulating and gingival NK cells, lack of DX5+ NK expansion and increased secretion of IFN-γ and IL-6 after culture. At the malignant stage of pancreatic cancer, hu-BLT tumor-bearing mice had the lowest secretion of IFN-γ from cells dissociated from the gingival tissues as compared to those from non-tumor bearing mice. Injection of NK cells into tumor-bearing mice increased IFN-γ secretion, and the secretion was similar or higher than those obtained by gingival cells from non-tumor-bearing hu-BLT control mice. The highest increase in IFN-g secretion was observed when tumor-bearing mice were fed with AJ2 probiotic bacteria and injected with the NK cells. Along with an increase in secretion of IFN-γ, injection of NK cells in the presence and absence of feeding with AJ2 in pancreatic tumor-bearing mice increased percentages of CD45+ and CD3+ T cells in oral gingival cells. Similar results were observed with oral tumors. In conclusion, these results indicated that oral cavity may mirror systemic disease, and provide a rationale for why cancer patients may be prone to suffer from diverse oral pathologies.